Ustanowienie i przeniesienie odrębnej własności lokalu w spółdzielni mieszkaniowej - Pietrzykowski, Krzysztof (PRAWO i WIĘŹ, 2023)
The author considers the relationship between the establishment and transfer of separate ownership of premises in a housing cooperative under the Law on Ownership of Premises, two development laws and the Law on Housing Cooperatives, as well as two Supreme Court decisions. He concludes that in the case of the creation of separate ownership of premises on the basis of a contract, we are dealing with both the establishment and transfer of the right of separate ownership of premises. The situation is different when the establishment of separate ownership of premises occurs on the basis of a unilateral legal act of the cooperative. The author emphasizes that the transfer of separate ownership of premises does not mean that this right arises ex lege in the course of liquidation, bankruptcy proceedings or enforcement proceedings in a housing cooperative. He states that only the transfer of separate ownership of premises is involved when separate ownership of premises has already been previously established.